Density and Mechanical Properties of Casuarina equisetifolia Wood Grown in Oromia Regional State, Bishoftu, Ethiopia - Mussa, Mahadi; Kelemwork, Seyoum; Wale, Mesganaw (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
Ethiopia's rapid expansion of urbanization, industrialization, modernization, and population growth has led to an insistently increase in the demand for wood for construction, furniture, and other end products. This study aimed to investigate the effect of tree height and the diameter tree section (sapwood and heartwood) on the density and mechanical properties of Casuarina equisetifolia timber. For this study, ten sample of C. equisetifolia trees were selected and harvested from Bishoftu, Oromia Regional State, Ethiopia. The collected sample logs were sawn into 3-cm-thick lumber, and sample specimens were prepared for density and mechanical properties testing. Sample specimens of heart and sapwood sections were prepared from the bottom, middle, and top portions of the tree for testing density, static bending (MOE and MOR), compression strength parallel to the grain, impact bending strength, and hardness strengths in tangential and radial directions according to ISO standards. The results revealed that tree height had significantly affected density and hardness strengths in tangential and radial directions. On the other hand, the diameter section (heart and sapwood) significantly affected the density, impact bending, and hardness strength in the radial direction. On the contrary, tree height and tree diameter section didn’t show a significant effect on MOE, MOR, and compression strength parallel to the grain. Due to the high density of Casuarina equisetifolia wood, it is very hard to convert into lumber, and the lumber is also difficult to machine. Based on the basic properties studied, Casuarina equisetifolia wood could be used for wood flooring, chipwood, particleboard, furniture, and other products such as tool handles.